Ferromagnetic resonance in exchange coupled bilayer films with stress anisotropy. (13th July 2016) - Zhang, Lei; Rong, Jianhong; Yun, Guohong; Wang, Dong; Bao, Lingbo
Abstract: Ferromagnetic resonance frequency and magnetic susceptibility in ferromagnetic/antiferromagnetic bilayer films with stress anisotropy are investigated using a ferromagnetic resonance method. In-plane anisotropy, weak and strong perpendicular anisotropy are taken into account in this theoretical model. The effect of stress anisotropy has been investigated; it was found that the resonance frequencies all increase for in-plane and weak perpendicular anisotropy, as the stress anisotropy field increases. In addition, the stress anisotropy field does not obviously affect the magnetic susceptibility for saturation field.